A evasão escolar na Educação para pessoas Jovens, Adultas e Idosas (EJAI), em uma escola no município de Ananindeua - CARMO, José Thiago Monteiro do (2023)
We know that education is a right of all and provided for in law. This research aimed to verify the presence of school dropout in the modality of Education for Young, Adult and Old People, in the initial stages of elementary school (1st and 2nd stage), between the years 2019 to 2022, in a school in the municipality of Ananindeua in the State of Pará. To demonstrate the reasons for the evasion and foster this discussion, with the possible causes that led the students to escape from the institution. For the development of this article, works by authors such as Arroyo (2017 and 2012), Cury (2020), Freire (2017, 2013 and 1997), among others and complementary texts that were essential for this research were used. Based on the bibliographic and exploratory field research, I observed and analyzed through the information collected (logbook) the impasses of evasion, within the perspective of the school. As results of this article, the problems related to the school were brought. It was found that there is a great need to keep students in the classroom, because evasion is a great challenge within this modality; and if the institution does not offer a pleasant space with interesting pedagogical proposals, the student will gradually lose the desire to study.